Through-thickness velocity profile of sheared sub-micron thick polymer melt - Wong,JSS; Ponjavic,A (2013)
The through-thickness velocity profile of a sub-micron thick polymer melt, under - elastohydrodynamic (EHL) conditions, has been recently obtained for the first time by the authors using photobleached imaging technique. In this work, the developed technique is applied to investigate the effect of shear rate on the evolution of velocity profile in polybutene (PB). The velocity profile of PB in an EHL contact severely deviates from the common linear assumption and exhibits shear localization. Depending on the average shear rate experienced by the polymer melt, interfacial slips and localized shear banding were observed.